William Collins and Eighteenth-Century English Poetry - Wendorf, Richard (Book collections on Project MUSE., 1981)
William Collins and Eighteenth-Century English Poetry was first published in 1981. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. William Collins (17211759) is one of several eighteenth-century poets who have received more attention for what they are said to have anticipatedthe full-blooded Romanticism of Wordsworth and Coleridgethan for what they have achieved. Collins's career as a poet was brief, but the handful of major poems that he wrote in the mid -1740s has stirred interest among critics intrigued by the complexity and obscurity of his work and by the illness and possible madness that prematurely ended his life. Combining historical scholarship with close readings of all Collins's poems, Richard Wendorf provides the most comprehensive and detailed study to be devoted to the work of this enigmatic figure and to the forces that shaped his literary career. In doing so, he places Collins within an eighteenth-century poetic context and shows that his gift for myth-making makes him a vital link between the mythic poetry of Shakespeare and Spenser and that of the Romantics. Wendorf's opening and closing chapters examine the relationship between Collins's life and his work, providing an authoritative discussion of his supposed madness and of the myths of insanity that clouded his reputation in the eighteenth and nineteenth centuries. Wendorf argues that Collins's madness is problematical at best, and that much recent criticism is a distortion of his major work, which explores the transcendent powers of the irrational forces within us but is not necessarily the product of madness itself. The book's central chapters trace Collins's development as a poet and offer fresh approaches to his major odes. In these mature poems he turned from his early interest in Augustan poetry to very different sources of inspiration and came to reject the ordered and unified natural world of Pope and Thompson.